Design and Testing of a Bungee Cord Based Launcher for LSU-02 UAV - Ari Sugeng Budiyanta; Fuad Surastyo Pranoto; Andreas Prasetya Adi; Agus Wiyono (Majalah Ilmiah Pengkajian Industri, 2022)
The LSU-02 is one of the unmanned aerial vehicles (UAVs) developed by LAPAN (now BRIN). It has a good endurance and flight range, i.e., it can fly for four hours and up to 200 km. However, the UAV needs a good and long runway to do the takeoff and landing operations. In real missions, sometimes it is hard to find the proper runway. Therefore, a method for taking-off without a runway, namely using a launcher, is required. The two most frequently used launcher systems are pneumatic launcher and bungee cord launcher. However, based on our experience using the launcher for LSU-03 UAV, a pneumatic launcher is considered less practical due to its complex and heavy construction. For the LSU-02 to be able to carry out missions in remote areas, a simpler and lightweight launcher is needed. Therefore the bungee cord-based launcher was chosen. The initial requirement for the launcher is that the launcher should able to push the LSU-02 with a maximum takeoff mass of 15 kg put on a 7 kg cradle (total mass 22 kg) and reach the launch speed of 15.2 m/s at the end of launching track. The simulation result shows that the launcher needs a time of 0.28 s to achieve a velocity of 15.2 m/s. Meanwhile, in 0.28 s, the UAV travel distance is 2.55 m. This is the minimum effective length required by the launcher. The real launcher was built with an effective length of 2.7 m. The launcher was tested for launching the LSU-02 with the UAV takeoff mass of 14.4 kg and the cradle mass of 7.5 kg (total of 21.9 kg). It was able to successfully launch the LSU-02 in 0.27 s with a travel distance on the launching rail of 2.5 m. Keywords:  Bungee cord, Design, Launcher, LSU-02, Testing, UAV